(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of counseling provided by healthcare workers on breastfeeding practices among women with normal delivery at Vinmec Times City Hospital in 2025. Subjects and methods: An analytical cross-sectional study was conducted on 250 women with normal delivery who attended antenatal classes from January to May 2025. Results: The mean attitude score towards breastfeeding increased from 3.52 ± 0.40 before counseling to 3.94 ± 0.55 after counseling sessions. The mean satisfaction scores were 4.52/5 points for antenatal classes, 4.49/5 points for prenatal counseling, and 4.55/5 points for hands-on breastfeeding guidance-all at a very high level. Conclusion: Counseling by healthcare workers significantly improved breastfeeding practices among women with normal delivery. This counseling model should be maintained and expanded, in combination with family and community support, to optimize access and maximize effectiveness.